PERAN PEREMPUAN DALAM PROSES PEMBUATAN KAIN TENUN SONGKET SAMBAS KALIMANTAN BARAT - utami, nunik esti (Universitas PGRI Yogyakarta, 2023)
This research aims to determine (1) The role of women in the process of making Sambas songket woven cloth, West Kalimantan. (2) Describe the history of Sambas songket cloth. The research method used in this research uses a literature review approach. Data collection is obtained by collecting and analyzing relevant historical sources from scientific journals, theses and digital sources related to the titles that have been studied by researchers. Data testing uses method triangulation and source triangulation techniques. The results of this research are (1) The role of women in Songket Sambas, namely a woman named Mrs. Sahidah who is a popularizer and activist of Songket Sambas Weaving. one of the pioneer figures of Sambas woven fabric, Mrs. Sahidah's mark of honor was the establishment of a weaving museum in Sambas (2) The history of the famous Sambas Songket Weaving began when the King of Brunei Darussalam gave a set of Sambas looms, so that the people around the palace had skills in weaving which was popularized During the reign of Raden Bima, the 2nd Sambas Sultan in 1668 - 1708, it was first used in traditional wedding ceremonies, namely songket sambas for weddings. In the beginning, Songket cloth was used to make woven cloth by Sambas women. The process of making Sambas Songket cloth began with the process of making the warp threads arranged parallel to each other. According to the width of the woven fabric, the weft threads are arranged crosswise with the warp threads.